Analisis Perbandingan Kualitas Buku Teks Bahasa Arab Ta’lim Al-Lughoh Al-Arobiyah Dan Al-‘Ashri : Kajian Isi, Penyajian Dan Bahasa - Khizanatul Hikmah; Ruli Astuti (Universitas Muhammadiyah Sidoarjo, 2018)
This study analyzed the comparison of the quality of Arabic textbooks Ta’im Al-Lughoh Al-Arobiyah and Al- Ashri based on the content review, presentation and language aspects aimed to describe and compare the quality of Ta'lim Al-Lughoh Al-Arobiyah and Al-'Ashri in terms of content, presentation and language. This research usedContent Analysis method. Respondents in this research are Arabic language teachers of SMA Al-Fattah Buduran and SMA Muhammadiyah 3 Tulangan. Data collection in this research using questionnaire filling technique, documentation and literature study. The results of this study are (1.1) Arabic Text Book al-'Ashri class X for SMA / SMK / MA Muhammadiyah published by PT. DMU has complied with standard of content / material review, presentation, and language aspects based on BSNP. This is indicated by the average score on the content / content assessment aspect 85.03%, presentation aspect 78.05%, and the language aspect 90.62%, (1.2) Arabic Textbook Ta'lim al-Lughoh al-'Arobiyah class X for SMA / SMK / MA written by Dr. D. Hidayat with the publisher Pt. Toha Putra has fulfilled the standard aspects of content / material review, presentation, and language based on BSNP. This is indicated by the average score acquisition on content / content review aspect 95,64%, presentation aspect 81,82%, and language aspect 96,49%.